(3eQBI GdReGf aj JhGQjN GdCYjGfs - (3jhSa Hf pbrRoChrZpdj (B- (3Ch bRZdj (B- (3GHf YHO Gddg, CHh GdeXaQ, TeS GdOjf, SHW CHj GdaQL GHf GdLhRj,J (B654 (3g` s ((3GdTQja MSf Hf CMeO GdHQOjfi GdMSfi s)
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdbOje GdedaGJ aUd (B: (3hHYO aEf GdaWQ GdSdjeI aUd (B: (3hebGUO GdfGS ai Pdc jNJda Ydi eG bO Cda s
(3BNQgG (B:s
(3hgh GdPi CNP eUGMa ehSi aLYdgG ai NGHjI ef fMGS hhVYgG hSO QCSgG hCJi HgG UNQI HjJ GdebOS aCfTbJ dg hHdZJ GdNGHjHI Je GdLRA GdChd s
(3HgG fXGe GdJYbjHIs
(3UaMI GdYfhGf eRNQaIs
(3ai GdeYgO fSN CNQi HQbe (B466 / 796/ 1221 / 1993 / 1994 (3JGQjN hajgG LejYkG GdYfhGf ai JGQjN GdCYjGfs
(3ajg VHW bdjd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B246 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B324s
Keywords: (3GdJGQjNs